2015
DOI: 10.1097/01.sa.0000459453.61119.bc
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Delirium in a Substudy of Cardiothoracic Surgical Patients in the BAG-RECALL Clinical Trial

Abstract: Background-Postoperative delirium in the intensive care unit (ICU) is a frequent complication after cardiac or thoracic surgery and is associated with increased morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 22 publications
2
43
0
Order By: Relevance
“…3 Is there anything that we as anesthesiologists can do to decrease the incidence of delirium? 5 Although Whitlock et al 4 also found a trend toward lower delirium incidence in patients enrolled in the BIS arm, neither the average ETAC, nor cumulative anesthetic exposure (e.g., MAC-hours), 8 nor the occurrence of deep anesthesia (BIS <20) is given for the BIS versus ETAC titration arms. In this issue of Anesthesia & Analgesia, Whitlock et al 4 examine whether using a BIS monitor decreases the incidence of delirium in cardiothoracic surgery patients.…”
mentioning
confidence: 95%
See 4 more Smart Citations
“…3 Is there anything that we as anesthesiologists can do to decrease the incidence of delirium? 5 Although Whitlock et al 4 also found a trend toward lower delirium incidence in patients enrolled in the BIS arm, neither the average ETAC, nor cumulative anesthetic exposure (e.g., MAC-hours), 8 nor the occurrence of deep anesthesia (BIS <20) is given for the BIS versus ETAC titration arms. In this issue of Anesthesia & Analgesia, Whitlock et al 4 examine whether using a BIS monitor decreases the incidence of delirium in cardiothoracic surgery patients.…”
mentioning
confidence: 95%
“…1 Today, the term postoperative delirium is often used to describe the mental state of many of these patients. Furthermore, one could argue that the difference in average ETAC (0.79 ± 0.12 vs 0.85 ± 0.11) between delirious and nondelirious patients is not clinically meaningful.Surprisingly, Whitlock et al 4 show that age-adjusted average ETAC during maintenance was inversely correlated with delirium; patients who received less inhaled agents were more likely to develop delirium. It is a common (and likely underrecognized) complication correlated with adverse outcomes including decreased quality of life and increased hospital and 6-month mortality.…”
mentioning
confidence: 97%
See 3 more Smart Citations